Employment Contracts for Foreign Workers in the Saudi System - A Legal Study of the Saudi Labor System 2025 AD/1446 AH - Al-Suqoor, Maneh Hussein Muhadhal (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to determine the effectiveness of the legal framework regulating employment contracts for foreign workers in the Kingdom of Saudi Arabia in protecting their rights and achieving balance in the contractual relationship with their employer. This research relied on a descriptive and analytical approach, describing and analyzing the legal texts related to employment contracts in the Saudi system, with a focus on the executive regulations and circulars issued by the Ministry of Human Resources and Social Development. It also analyzes a set of previous studies and relevant judicial rulings, with the aim of developing a comprehensive understanding of the practical problems associated with the implementation of these contracts. The research also relies on a comparative approach in some parts, examining the similarities and differences between the Saudi system and the labor systems in force in some Gulf countries, in order to extract the essential differences and benefit from successful experiences in this field. The study concluded that: (1. The employment contract for foreign workers in the Saudi system is one of the contracts that receives significant attention from government authorities, with the aim of ensuring the rights of all concerned parties, whether the foreign worker or the employer. The Saudi system has established a comprehensive legal framework to regulate labor relations. This reflects the Kingdom's commitment to providing a fair and safe work environment for all workers, in line with human rights principles and strengthening the national economy. 2. Contract conclusion procedures are considered one of the fundamental pillars upon which the legal system in the Kingdom is based, as these procedures ensure transparency and equality between foreign workers and employers. 3. Electronic systems, such as the "Qiwa" platform, have contributed to facilitating the procedures followed, increasing the efficiency and speed of issuing visas and documenting contracts. However, there remain some challenges that some foreign workers may face, such as difficulties in understanding the legal rights or obligations related to residency or work).
Keywords: contract; employment; worker; foreigner; Saudi system